(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This study was carried out to investigate the effect of feeding Awassi lambs different ratios of concentrate: wheat straw (C: R) on blood parameters. Five pellets of total mixed rations (TMR) containing 30:70, 40:60, 50:50, 60:40 and 70:30 of C: R ratios were prepared and offered to lambs ad libitum. The results showed that increasing the C: R ratio significantly (P<0.01) increased the blood glucose. Higher concentration, 75.38 and 75.59 mg/100 ml were recorded in blood samples withdrawn from lambs fed on pellets containing 60:40 and 70:30 of C: R ratios respectively. similarly, those blood samples were characterized with higher (P<0.01) concentrations of total protein and triglycerides. With regard to urea nitrogen, higher (P<0.01) concentration, 44.15, 42.68 and 44.98 mg/100 ml were detected in blood samples withdrawn from lambs fed pellets containing 50:50, 60:40 and 70:30, respectively.